Advance Oracle Clinical Software tool used in clinical research from patient data collection to data base lock. (March 2013) - Kunithala, Vasanth Kumar; Kabeer, Ahamed; Vemula, Sateesh Kumar
Abstract This article is based on how the Oracle Clinical Software tool is used in clinical research. It is known that conducting research is a costly and time consuming process as it requires extra human resources, many software tools, and thorough knowledge of software in clinical research. This particular software helps in improving the trial performance and reduces the cost to the company. This article mainly describes the process of patient enrollment, data entry, data validation, E-data & SAE reconciliation, coding, discrepancy management, quality control process and data lock. Pharma Industries follow different methods for collecting, transferring, and storing patients data. Providing the knowledge of software tools to the persons who are involved in the trails will help them in simplifying their work. The objective is to provide complete knowledge of the Oracle Clinical Software tool by using proper guidelines of clinical trials. This also gives a complete idea of responsibilities and the functionality of data operation as well as tools analysis which would also help in tackling the risk profiles. All the above-mentioned applications would make one extract appropriate and consistent data of a patient, while submitting FDA.